Implementation of Sphinx/Lynx as daily QA equipment for scanned proton and carbon ion beams. Issue 4 (27th January 2023) - Grevillot, Loïc; Moreno, Jhonnatan Osorio; Fuchs, Hermann; Dreindl, Ralf; Elia, Alessio; Bolsa‐Ferruz, Marta; Stock, Markus; Palmans, Hugo
Abstract: Purpose: Reporting on the first implementation of a proton dedicated commercial device (IBA Sphinx/Lynx) for daily Quality Assurance (QA) of scanned proton and carbon ion beams. Methods: Daily QA trendlines over more than 3 years for protons and more than 2 years for carbon ions have been acquired. Key daily QA parameters were reviewed, namely the spot size and position, beam range, Bragg peak width, coincidence (between beam and imaging system isocenters), homogeneity and dose. Results: The performance of the QA equipment for protons and carbon ions was evaluated. Daily QA trendlines allowed us to detect machine performance drifts and changes. The definition of tolerances and action levels is provided and compared with levels used in the literature. Conclusion: The device has been successfully implemented for routine daily QA activities in a dual particle therapy facility for more than 2 years. It improved the efficiency of daily QA and provides a comprehensive QA process.